Beyond the learning curve : the construction of mind - Speelman, Craig P. (Oxford University Press, 2005)
By reviewing the literature on skill acquisition, the authors propose a new theoretical approach to understanding the role of learning in behaviour. They present a new perspective on psychology - one that identifies universal principles underlying all behaviours.